Loanword adaptation parameters in contact: The case of -ING Anglicisms in Russian - Akishev, Timur (Lingua Posnaniensis, 2026)
This study focuses on a corpus-based description of the process of linguistic adaptation of nominal English loanwords in Russian containing the deverbal suffix -ING, transliterated into Russian as инг /ɪng/. 89 loanword items were analyzed in terms of their linguistic characteristics, such as morphological structure and frequency of occurrence in the corpus. The study discusses the complex nature of the lexical items that are transferred from one language into another through ongoing language contact. The corpus-based analysis included such procedures as the search for any relevant items within a given time frame in a selected corpus, the identification and assigning of language-related characteristics to the items elicited from the corpus, and the statistical procedure that aimed to determine and describe the relationships that exist, or are likely to exist, between different types of characteristics of the loanwords.